2011
DOI: 10.1007/s11237-011-9169-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of liquid hexadecane with selective microwave heating of the catalyst

Abstract: The pyrolysis of liquid n-hexadecane was studied on various catalysts with selective microwave (MW) heating of a catalyst possessing much greater microwave absorption capacity than the long-chain hydrocarbon studied. This method permits rapid heating of the catalyst to temperatures much higher than 400°C, leading to reflux of the liquid substrate, movement of the catalyst granules within the substrate, and chemical transformations (cracking) of hexadecane. High pyrolysis selectivity relative to a-olefins was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…It could also promote certain heterogeneous reactions by heating the pyrolysis-volatiles evolved from the pyrolysis of waste oil, leading to a different product composition observed in the pyrolysis products. It has been reported that the metal-containing char product could potentially be used as an inorganic catalyst in thermal cracking processes [20]; the presence of some metals (e.g., Fe, Ni) in the char could have a catalytic effect on some of the heterogeneous reactions (e.g., methane decomposition reaction) that occurred as have been reported by others in pyrolysis studies of other materials [19,21,22]. In addition, the use of char produced from pyrolysis processes as a catalyst has recently shown advantages in transforming biomass materials (e.g., sewage sludge, coffee hulls) into valuable gases such as H 2 and syngas in microwave pyrolysis process [16,[23][24][25]; the waste materials were mixed with small amounts of the char and subjected to pyrolysis treatment.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…It could also promote certain heterogeneous reactions by heating the pyrolysis-volatiles evolved from the pyrolysis of waste oil, leading to a different product composition observed in the pyrolysis products. It has been reported that the metal-containing char product could potentially be used as an inorganic catalyst in thermal cracking processes [20]; the presence of some metals (e.g., Fe, Ni) in the char could have a catalytic effect on some of the heterogeneous reactions (e.g., methane decomposition reaction) that occurred as have been reported by others in pyrolysis studies of other materials [19,21,22]. In addition, the use of char produced from pyrolysis processes as a catalyst has recently shown advantages in transforming biomass materials (e.g., sewage sludge, coffee hulls) into valuable gases such as H 2 and syngas in microwave pyrolysis process [16,[23][24][25]; the waste materials were mixed with small amounts of the char and subjected to pyrolysis treatment.…”
Section: Introductionmentioning
confidence: 77%
“…Moreover, thermal energy is targeted only to microwave receptive materials and not to gases within the heating chamber or to the chamber itself. It can promote certain chemical reactions by selectively heating the reactants, leading to a more uniform temperature profile and improved yield of desirable products [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, energy is targeted only to microwave receptive materials and not to gases within the heating chamber or the chamber itself. It can promote certain chemical reactions in a way that is not possible in conventional processing by selectively heating the reactants, leading to a more uniform temperature profile and improved yield of desirable products [30,37,59,60].…”
Section: Microwave-heated Pyrolysis Compared To Conventionally-heatedmentioning
confidence: 99%
“…Thus, a material with a moderate value of ' and a high value of " (and so a high value of tan ) is considered as a good microwave receptor with high capability in converting electromagnetic energy into thermal energy. Typical materials that exhibit good dielectric properties with a high value of tan are carbon materials and inorganic oxides [37], whereas materials such as plastics are considered as 'transparent' to microwaves because they do not possess a sufficiently high dielectric loss factor (") to allow for dielectric heating [35].…”
Section: Microwave Heating Mechanismsmentioning
confidence: 99%
“…It was revealed that the use of carbon-based materials (e.g., particulate-carbon, char produced from pyrolysis) as the microwave receptor offers a number of advantages over conventional pyrolysis techniques. Carbon-based materials are good microwave-absorbents [37] that can be used to heat neighbouring substances (particularly those that are transparent to microwaves) to high temperatures at a fast heating rate by microwave radiation [38,61,64]. In addition, the use of carbon-based materials as a reaction bed provides a highly reducing chemical environment, which removes oxygen functionalities from the treated substances and decreases the formation of undesirable oxidised species during the pyrolysis [7,44].…”
Section: Microwave-heated Pyrolysis Compared To Conventionally-heatedmentioning
confidence: 99%